Kelayakan Hair Mask Dari Saripati Stroberi dan Minyak Kelapa Murni (VCO_ Untuk Perawatan Rambut Kering - Hasibuan, Nurhayya Putri; Khairani, Afdila; Maidi, Asdita; Rauzati, Nursandrina; Dewi, Siska Miga; Saputra, Indra; Safitri, Dewi (Jurnal Tata Rias, 2023)
Hair mask coconut oil and strawberries is a cosmetic based on pure coconut oil VCO and strawberries which is used in the treatment of dry hair creambath which is useful for nourishing and reducing dry hair problems. In the process of making hair masks, it is divided from basic ingredients, including virgin coconut oil (VCO) and strawberries. This study aims to provide insight to the public that pure coconut oil (VCO) can be used as a cosmetic for hair, and can also be formulated with strawberries as a hair mask which functions to treat dry hair. All of this information is made shorter, concise, and clear in language that is easily understood by the public, that is, everyone from all walks of life who wants to use a hair mask. The data analysis technique in this study is the texture test, aroma test, color test and preference test. The results of this organoleptic feasibility test met the validation criteria with a result obtained of 60%, so it can be concluded that the hair mask is suitable for use by the public.